Reopening with Resilience - UNICEF Innocenti Research Centre (United Nations, 2021)
The COVID-19 pandemic led to school closures around the world, affecting almost 1.6 billion students. The effects of even short disruptions in a child’s schooling on their learning and well-being have been shown to be acute and long lasting. The capacities of education systems to respond to the crisis by delivering remote learning and support to children and families have been diverse yet uneven. This report reviews the emerging evidence on remote learning throughout the global school closures during the COVID-19 pandemic to help guide decision-makers to build more effective, sustainable, and resilient education systems for current and future crises.